“Efecto de la variabilidad climática en el manejo de soca de arroz (oryza sativa), bajo diferentes densidades de siembra en bosque seco tropical en el distrito de cacatachi Región San Martín” - Ipanama Solano, Fernando Larsson (2014)
The research entitled "Effects of climate variability in the management of soca rice (Oryza sativa) variety Capirona different stocking densities in Cacatachi district, San Martin Region, aimed to collect and analyze weather data historical pattern of 1986 - 2005 against the period evaluated from January to April 2006, to collect and analyze the temperature and soil moisture through Aquater - 300 in the evaluated period February - April 2006, at different times: 7:00 am, 12:00 noon. 6:00 pm So as to determine the influence of climate variability in the behavior of the soca and evaluate the effect of planting density. Statistical block design was used at random (RCBD) with four treatments and three replications, making a total of 12 experimental units. The results indicate that an increase of O, 1 ºC in the assessment period and this value was recorded, explains that a slight climatic variation was recorded, affecting management behavior of Soca in rice cultivation in the Capirona variety, affecting the performance of traditional planting spacing 25 x 25 cm, to obtain lower performance relative to other densities evaluated in this research. Keywords: variability, climate, temperature, precipitation, soca, variety, performance, production, Capirona, increase.